Coping strategies in victims, bullies, bullies-victims and bystanders of cyberbullying - Martínez-Monteagudo, María C.; Escortell-Sánchez, Raquel; Delgado, Beatriz (10th International Conference on Education and New Learning Technologies (EDULEARN), 2021)
The aim of the present study was to carry out a documentary review about the cyberbullying phenomenon. Specifically, the investigation was focused on existing research on the coping strategies of victims, bullies, bullies-victims and bystanders, in samples of students from 10 to 21 years old. The search was made through the hermeneutic method, taking as samples indexed databases, such as Scopus, Scielo, Proquest or Web of Science. The evidences found provide information about the coping mechanisms of each of the roles involved, highlighting the role of bystanders as a determining factor when perpetuating harassment by the harassers of the victims. This information acquires great importance when it comes to understanding this phenomenon, as well as in the identification of possible cases of cyberbullying based on the behaviors of those involved.
Ponencia del congreso: 10th International Conference on Education and New Learning Technologies (EDULEARN)
Keywords: cyberbullying; coping strategies; victims; bullies; bystanders; WOS(2)